Ápice: plan parcial de conexión y rehabilitación eco productivo Sabana Centro (2019)
The partial plan is in an area of ​​one kilometer distance, located towards the entrance of Subachoque by the 50th route, more precisely in Puente Piedra, where the main access road is the one that communicates with all the municipalities of the savannah center . In addition, it is important the proximity to the El Dorado airport and the new airport raised in Madrid as a key to the proposed intervention, due to the demand of tourists and its large floricultural production. At a specific level, the partial plan proposes to potentiate and reactivate its main element of production and economic income such as flower crops and in this way, give added value to this product through perfumes, creams, aromatizers and others, which reflect the woman and the whole issue is directed towards them.